Assessment Of Money Illusion Impact On Individuals’ Economic Behaviour In Lithuania - Jureviciene, Daiva; Markelova, Jekaterina (European Scientific Journal, ESJ, 2016)
Behavioural economics was in a process of rapid development in the last century. One of behavioural phenomenon discovered by economists is money illusion – an inclination to make biased decisions based on nominal rather than real monetary values. This illusion influences individuals’ perception of money-related processes and, hence, their economic behaviour. Euro illusion concept, which represents money illusion in countries that adopted the euro, became commonly used after money illusion has been identified and studied in a number of Euro zone countries. Money illusion has not been deeply discussed in Lithuania. The euro introduction in 2015 provides an additional reason to study its impact on Lithuanian citizens. The purpose of the paper is to evaluate money illusion impact on individuals’ economic behaviour in Lithuania after assessment whether Lithuanians experience it. Analysis of scientific literature, experimental study and statistical methods were applied. It was found that citizens are prone to money illusion, which causes irrational economic behaviour. Despite difficult adaptation to the euro, Lithuanians do not experience euro illusion. Newly collected data on money illusion in Lithuania suggests critical evaluation of individuals’ economic behaviour. Performance of such experiment has some limitations as problems presented in a survey are hypothetical and decisions made by participant may not extend to real world. In addition participants may bear in mind their own assumptions like personal experience (e.g. income, savings, debts etc.) which could affect their decisions.